Evaluation of architecture student classroom communication at Universiti Kebangsaan Malaysia - Muhammad Faiz Bukhori,; M. F. I. Mohd Nor,; Mazlan Mohd Tahir,; Abdul Halim Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Classroom communication is a very important and complex aspect in teaching and learning. Its complexity is attributed to a host of factors that include participants, messages, encoding, decoding, and channels. Not much is currently known concerning classroom communication in the context of architecture education in Malaysian universities. This paper evaluates classroom communication of students undertaking architecture degree programs at Universiti Kebangsaan Malaysia. Four factors of student classroom communication were investigated to understand student abilities and issues in classroom communication. Forty-four students undertook the self administered survey. The majority of the students exhibited good non-verbal communication practices, and scored favourably in the aspect of adapting the way they communicate to others. However, students seemed to have some difficulty to express ideas in class presentations. Additionally, some students appeared to be handicapped in actively participating and leading class discussions. Last but not least, a number of students were not comfortable in using English in the classroom, but not to the extent of hindering them in participating in classroom discussions. Further studies are needed to uncover classroom communication issues in student learning among architecture students at Universiti Kebangsaan Malaysia.